Acceptability of AAI from the Perspective of Elderly Clients, Family Members, and Staff-A Pilot Study - Machová, Kristýna; Procházková, Radka; Konigová, Petra; Svobodová, Ivona; Přibylová, Lucie; Vadroňová, Mariana (International journal of environmental research and public health, 2020)
Although animal-assisted interventions (AAIs) are increasingly part of comprehensive rehabilitation and many of its effects are already well described, the methodology for performing AAI depends on the specific patient, animal, and treatment objective. Acceptability of AAI from all involved members is a little explored area. Thus, 214 respondents (32 AAI clients, 146 family members, and 36 healthcare and social care workers; 98 males, 116 females; mean age 46.3 years (±16.5 SD)) completed a list of statements focused on AAI with a dog. This list was distributed directly in nursing homes, retirement homes, and in households with home hospice care. All statements were rated on a Likert scale of 0-3. The results show that AAI is generally very well received, with over 90% of respondents considering AAI to be beneficial. The perception of AAI and trusting the handler with their dog was evaluated very positively, as well as possible concerns about hygiene. The results were in many cases affected by demographic factors of the respondents (age, gender, role in AAI, education, and size of settlement). It seems appropriate in future studies to focus on the attitude of individual groups, and thus advance the methodology of implementing AAI.
Keywords: Animals; hygiena; Female; Hygiene; rodina; ženské pohlaví; služby domácí péče; Home Care Services; lidé; Pilot Projects; pilotní projekty; Dogs; Nursing Homes; Male; Aged; Animal Assisted Therapy; Family; zooterapie; lidé středního věku; senioři; zvířata; mužské pohlaví; Middle Aged; psi; pečovatelské domovy; Humans